PABRIK GASOLINE DARI METANOL DENGAN FIXED BED MTG PROCESS KAPASITAS 981.000 TON/TAHUN - , HANA FITRIA PRASASTI, Dr. Ir. Bardi Murachman, S.U., DEA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Gasoline and Liquefied Petroleum Gas are energy resource that commonly used in daily life and industry. Most gasoline and LPG are made from fractional distillation of crude oil-which its reserves are reduced every day. These products contain high sulfur, poor octane number, and need extra treatment for removing the heavy metals. The new technology called MTG (Methanol to Gasoline) Process with gamma alumina and ZSM-5 catalyst can be the answer of these issues. C1-C10 hydrocarbon and aromatic called durene are formed from methanol two series of adiabatic fixed bed reactors. First reactor convert methanol to dimethyl ether (DME) and the second reactor convert the DME to C1-C10 hydrocarbon and the aromatic. Gamma alumina catalyst is used in the first reactor, the second used ZSM-5 catalyst. These series of reaction occurs in high temperature, the temperature out of the second reactor is about 1100K with 15,6 atm pressure. This MTG plant is designed for annual capacity of 981.000 ton/year and operates continuously for 330 days. This plant requires raw material methanol in amount of 3.490.000 ton/year. This futuristic plant is planned to be built in Bontang, Kalimatan Timur. The land required for this plant is 148.200 m2. The employers needed to run this plant are 216 persons. From economic analysis it is obtained that, this plant requires a fixed capital investment of US$ 153.094.754,28 and Rp 459.078.348.680,99. For working capital as much as US $ 188.397.828,57 and Rp 1.587.807.219.096,21. This plant will earn a before taxes profit Rp 750.943.524.898,07 with taxes rate of 50%, it will earn an after taxes profit of Rp 375.471.762.449,04. A feasible study concludes an Return on Investment (ROI) before taxes of 35,0% & and ROI after taxes 17,5%. Pay Out Times (POT) before taxes is 2,27 years and POT after taxes is 3,77 years. Discounted Cash Flow is 13,40%. Break Even Point is 57,11 % and Shut Down Point is 40,50 %. Based on this economic study, this gasoline from methanol plant is economically feasible.